Pencegahan Anemia dan Stunting Melalui Pemberdayaan Peran Remaja dengan Kader Yowana Bali (KAYOBI) - Adirinata, I Komang Pasek; Suardana, I Wayan; Ruspawan, Dewa Made; Hartati, Ni Nyoman; Sukarja, I Made; Ribek, Nyoman (Jurnal Gema Keperawatan, 2025)
Anemia and stunting are significant public health problems in Indonesia, especially among adolescents. The Yowana Bali Cadre Program (KAYOBI) aims to increase adolescents' knowledge and awareness about the prevention of anemia and stunting. This study uses a quantitative design with a cross-sectional approach. Data were collected from 31 respondents, using purposive sampling techniques. Knowledge assessment was conducted through questionnaires, and data analysis was conducted by Chi-square test  to determine the relationship between  KAYOBI website access and respondents' knowledge level. The findings showed that 74,2% of the participants were women, and 64,5% of them accessed  the KAYOBI website. The results of the respondents' knowledge assessment before accessing the KAYOBI website showed that 23,1% of respondents had adequate knowledge about anemia and stunting. Chi-square analysis  showed a significant relationship between website access  and knowledge level, where individuals who did not access websites were 20 times more likely to engage in poor prevention practices.  KAYOBI's website is rated good in terms of usability, quality of information, and interaction. This research emphasizes the importance of continuing education initiatives and community involvement in combating anemia and stunting, as well as the need for more effective health promotion among adolescents. The KAYOBI program is effective in increasing adolescents' knowledge about anaemia and stunting prevention, and access to information through the website contributes to better prevention practices.